Asymptomatic bacteriuria and urinary tract infections in kidney transplant recipients. Issue 6 (December 2020) - Coussement, Julien; Kaminski, Hannah; Scemla, Anne; Manuel, Oriol
Abstract : Purpose of review: Urinary tract infection (UTI) is the most common infection in kidney transplant recipients (KTRs). Several elements increase the risk of UTI and/or modify its clinical presentation among KTRs (e.g. immunosuppressive therapy, kidney allograft denervation, and use of urinary catheters). Also, KTRs may have UTIs because of difficult-to-identify and/or difficult-to-treat organisms. We provide an overview of the current knowledge regarding bacterial UTIs in KTRs, with a focus on recent findings. Recent findings: There is accumulating evidence from clinical trials that screening for and treating asymptomatic bacteriuria is not beneficial in most KTRs (i.e. those who are ≥1–2 months posttransplant and do not have a urinary catheter). These patients have a point-prevalence of asymptomatic bacteriuria of only 3% and treating asymptomatic bacteriuria probably does not improve their outcomes. There is no clinical trial evidence to guide the management of symptomatic UTI in KTRs. Several important clinical questions remain unanswered, especially regarding the management of posttransplant pyelonephritis and the prevention of UTI in KTRs. Summary: Despite its frequency and associated morbidity, UTI after kidney transplantation is an understudied infection. In an era of increasing antimicrobial resistance and limited resources, further research is needed to ensure optimal use of antimicrobials in KTRs with UTI.